Pengaruh Profitabilitas Terhadap Struktur Modal Selama Pandemi Covid-19 (Studi pada Industri Barang Konsumen Primer di Bursa Efek Indonesia): (Studi pada Industri Barang Konsumen Primer di Bursa Efek Indonesia) - Novita K. Adji; Lusianus Heronimus Sinyo Kelen (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This study examines how profitability affects capital structure during the Covid-19 Pandemic. The population of this study is all firms that are members of the primary consumer goods industry on the Indonesia Stock Exchange (IDX). The sampling method used in this study was purposive sampling, and a total of 87 firms were obtained. The data analysis technique used is simple linear regression. The results of this study indicate that profitability has a negative and significant effect on capital structure, so it can be concluded that the pecking order theory is proven and applies to firmss in managing their capital structure.